Rediscovery of Rhipidomys ochrogaster J.A. Allen, 1901(Cricetidae: Sigmodontinae) with a redescription of the species - Pacheco, Víctor; Peralta, María (Zootaxa, 2011)
Rhipidomys ochrogaster is a poorly known sigmodontine rodent from the Yungas of southeastern Peru, known only from a few specimens collected more than 110 years ago. This work reports a new specimen from Yanacocha, Puno, Peru, collected on 22 May 2010; provides a morphological description and comparisons with R. leucodactylus and R. gardneri; characterizes the habitat; and presents data on the diet of the species. This discovery stresses the urgent need for additional inventory work in the region, in order to document its biodiversity.